Strategic Management Indicators for Sustainable Road Traffic Management - Almazrouei, Abdulla; Yassin, Azlina Md; Memon, Aftab Hameed (International Journal of Sustainable Construction Engineering and Technology, 2021)
Human is very critical and important asset of any nation. Human security is the prime need. Also, at organizational level, the business success depends on the human efficiency. Hence, strategic management is very important to achieve effective performance. This paper assessed various indicators and attributes of strategic management. However, the limitation of this study was to focus on strategic management used in traffic management used by public security sector of Abu Dhabi. Evaluation involved 29 common attributes of strategic management identified from literature. These were categorized into five indicators as learning & training; traffic setting; emergency response; road engineering & vehicle safety; and strategies being enforced. Analysis of the data collected through Questionnaire survey with officials involved in traffic management was done with mean score method. Results of the analysis showed that review and develop a driver training program and licensing mechanism is the top ranked attribute in the domain of learning & training. The respondents highlighted effective traffic control in pedestrian and cyclist safety areas and seatbelts as very useful in the indicator traffic setting. Top indicators in the indicator emergency response are development of effective systems for geographical positioning of traffic accidents, and spreading a culture of prioritising emergency vehicles in emergency situations. Develop an integrated traffic safety management system (ITSMS) is the most useful attribute related to road engineering & vehicle safety indicator. While in the indicator strategies being enforced, the respondents mentioned that the attribute at top rank is developing smart traffic settings to minimize the accidents.